Comportamiento de la Biometría Hemática en pacientes con COVID-19 - Mullo Ramírez, Jackeline Margoth (2022)
ABSTRACT: The main objective of this study was to investigate the behavior of blood biometry in patients with COVID-19, for the determination of hematological alterations. By means of a bibliographic review, which was carried out in different scientific databases. The methodology was qualitative, descriptive and retrospective with a population of 60 scientific articles from which a sample of 25 useful bibliographic sources related to the object of study was taken, information was collected from the following scientific databases; Scopus: (5), Britannica Academic: (2), Britannica Moderna: (3), Scielo: (3), MEDLINE: (3), PUBMED: (4), EMBASE: (3), ELSEVIER: (2), published in the last 5 years to meet the inclusion criteria and respond to the study problem. Data collection was carried out by means of content analysis and interpretation of the results obtained in the bibliographic searches, and only useful information was selected for inclusion. The quality of studies was assessed by the PeDro Scale. The articles searched were in Spanish and English. The results obtained were that lymphocytes play a decisive role in the maintenance of immune homeostasis and inflammatory response throughout the body. Understanding the mechanism of reduced blood lymphocyte levels is expected to provide an effective strategy for the treatment of COVID-19 and it was also observed that low platelet count is associated with an increased risk of severe disease and mortality in patients with COVID-19. Keywords: lymphocytes, platelets, blood biometry, lymphopenia, COVID-19.